(untitled) (Research, Society and Development, 2021)
The objective of the research presented in this article was to perform the modeling of geological and geotechnical properties in the subsoil of a neighborhood in the city of Belém do Pará, using percussion drilling, using geostatistics as a tool. To achieve the objective, the cataloging of the technical collection was carried out, containing 101 percussion survey bulletins. A data base was created containing data on geographic coordinates, soil type, depth of soil layers, ground water level and Penetration Resistance Index (NSPT), according to NBR 6484/2001. The data were analyzed in a GIS environment (Geographic Information System) with Open Source software such as SGEMS (Standford Geostatistical Modeling Software) for geostatistical analysis and the Qgis software for cartographic analysis. Two disparate zones were distinguished in the study region, called Zone A and Zone B. Zone A is considered to be a region with the highest soil resistance indexes and Zone B is a region with the lowest resistance indexes, as shown in the maps . In the region there are organic clays of low resistance in the vicinity of the floodplain areas, where the streams were located in the past. However, these locations were rectified during the Urbanization process. And currently, the regions of low resistance described in the results of this research are located.